The Effect of Storybook-Based Shared Reading Learning Approach on Reading Interest and Indonesian Language Learning Outcomes in Class V Elementary School Students - Balqis Balqis; Tarman A. Arif; Haslinda Haslinda (Universitas Muhammadiyah Enrekang, 2023)
This study aimed to determine the effect of storybook-based Shared Reading leaming approach on reading interest and Indonesian language learning outcomes in fifth grade elementary school students, Makassar District. This research was a quantitative research using quasi-experimental method. This study deployed a non-equivalent control group design. Data collechon techniques in this study were through observation, questionnaires and tests. The population in this study were all fifth grade elementary school students in the Makassar district. The samples in this study were MIM 11 Bara-Baraya as many as 33 students as the experimental class and MIM B Maccini 30 students as the control class The data analysis technique used was the independent sample t-test and the multivariate analysis of variance, which had previously been tested for prerequisites, namely normality and homogeneity. The results of this study indicated that reading interest and Indonesian language learning outcomes which being given treatment in the form of the application of a shared reading approach compared to students who did not The storybook-based shared reading learning approach was said to bo influential because it increased reading interest and Indonesian language learning outcomes Based on the results of the independent sample t-test on hypothesis 1, the sig value was obtained of 0.003 0.05, it can be stated that H0 is rejected and Ht is accepted, in hypothesis II the sig value is obtained of 0.00 -0.05, it can be stated that HO is rejected and H1 is accepted And the results of the Manova test, obtained the value of sig 0.00<0.05, it can be stated that HO is rejected and H1 is accepted. because the significance value is less than 0.05. Based on this, it can be stated that the storybook-based shared reading learning approach impacted on reading interest and Indonesian language learning outcomes at the fifth graders elementary school students in Makassar.